Ramucirumab or placebo plus erlotinib in EGFR‐mutated, metastatic non‐small‐cell lung cancer: East Asian subset of RELAY. Issue 12 (14th October 2020) - Nishio, Makoto; Seto, Takashi; Reck, Martin; Garon, Edward B.; Chiu, Chao‐Hua; Yoh, Kiyotaka; Imamura, Fumio; Park, Keunchil; Shih, Jin‐Yuan; Visseren‐Grul, Carla; Frimodt‐Moller, Bente; Zimmermann, Annamaria; et al.
Abstract: In the global phase III RELAY study, ramucirumab plus erlotinib (RAM + ERL) demonstrated superior progression‐free survival (PFS) to placebo plus erlotinib (PL + ERL) in untreated patients with epidermal growth factor receptor ( EGFR ) mutation‐positive metastatic non‐small‐cell lung cancer (NSCLC) (hazard ratio (HR) [95% CI]: 0.59 [0.46‐0.76]). This prespecified analysis assessed RAM + ERL efficacy and safety in the RELAY subset enrolled in East Asia (Japan, Taiwan, South Korea, Hong Kong). Randomized (1:1) patients received oral ERL (150 mg/d) plus intravenous RAM (10 mg/kg) or PL Q2W. Primary endpoint was PFS (investigator‐assessed). Key secondary endpoints included objective response rate (ORR), disease control rate (DCR), duration of response (DoR), overall survival (OS), and safety. Exploratory endpoints included biomarker analyses and time to second progression (PFS2). Median PFS was 19.4 vs 12.5 mo for RAM + ERL (n = 166) vs PL + ERL (n = 170) (HR: 0.636 [0.485‐0.833]; P = .0009). The 1‐y PFS rate was 72.4% vs 52.2%, respectively. PFS benefit was consistent in most subgroups, including by EGFR mutation (Ex19del, Ex21.L858R). ORR and DCR were similar in both arms, but median DoR was longer with RAM + ERL. OS and PFS2 were immature at data cut‐off (censoring rates, 81.2%‐84.3% and 64.1%‐70.5%, respectively). Grade ≥ 3 treatment‐emergent adverse events were more frequent with RAM + ERL (70.7%) than PL + ERL (49.4%). Adverse events leading to treatment discontinuation were similar in both arms (RAM + ERL, 13.3%; PL + ERL, 12.9%), as were post‐progression EGFR T790M mutation rates (43%; 50%). With superior PFS over PL + ERL and safety consistent with the overall RELAY population, RAM + ERL is a viable treatment option for EGFR ‐mutated metastatic NSCLC in East Asia. Abstract : This RELAY subset analysis of EGFR ‐mutated NSCLC patients enrolled in East Asia demonstrated superior progression‐free survival (PFS) for ramucirumab plus erlotinib compared with placebo plus erlotinib (median PFS 19.4 vs 12.5 mo, HR [95% CI]: 0.636 [0.485‐0.833], P = .0009). The PFS benefit was accompanied by a consistent benefit for ramucirumab plus erlotinib in secondary, exploratory, and subgroup analyses and a manageable safety profile (consistent with the global RELAY study population). These results support the RELAY regimen as an effective and safe treatment option in the East Asian population.